2016
DOI: 10.1130/g38242.1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical amorphization, flash heating, and frictional melting: Dramatic changes to fault surfaces during the first millisecond of earthquake slip

Abstract: The evolution of fault strength and behavior during the initial stages of slip plays an important role in driving the onset of instability and fault weakening. Using small-displacement triaxial experiments on quartz sandstone, this study highlights the rapid onset of microstructural change on fault interfaces and identifies new evidence for an evolution in physical processes with increasing slip and velocity. Pre-ground fault surfaces have been slipped over a range of velocities (0.36 µm s–1 to 18 cm s–1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 19 publications
1
40
0
Order By: Relevance
“…This is similar to the findings of Engelder (1976) for sliding on ground surfaces of Westerly granite. Friedman et al (1974) and more recently Hayward et al (2016) reported the occurrence of localized patches bearing small tendrils of glass produced by high-speed frictional melting (e.g., during stick-slip events) in high temperature experiments on sandstones at normal stress conditions overlapping with those used in the present experiments. From microscopic examination of the slip surfaces we did not find any evidence of such occurrences, but this does not preclude the possibility that frictional melting may have developed locally.…”
Section: /2017jb014858mentioning
confidence: 51%
“…This is similar to the findings of Engelder (1976) for sliding on ground surfaces of Westerly granite. Friedman et al (1974) and more recently Hayward et al (2016) reported the occurrence of localized patches bearing small tendrils of glass produced by high-speed frictional melting (e.g., during stick-slip events) in high temperature experiments on sandstones at normal stress conditions overlapping with those used in the present experiments. From microscopic examination of the slip surfaces we did not find any evidence of such occurrences, but this does not preclude the possibility that frictional melting may have developed locally.…”
Section: /2017jb014858mentioning
confidence: 51%
“…This is interpreted to result from either a lower orientation contrast from a nonuniform reflection of low‐loss BSEs in the noncrystalline structure or a reduced Z contrast (representing mean atomic number) due to the lower density of the glass compared with its crystalline equivalent. The amorphous structure of this material has been confirmed using transmission electron microscopy (Hayward et al, ).…”
Section: Resultsmentioning
confidence: 84%
“…The evolution of fault strength during the initial stage of slip plays a crucial role in the fault-weakening processes (Hayward et al, 2016). Indeed, flash melting occurs at the onset of sliding (Beeler et al, 2008;Nielsen et al, 2008;Rice, 2006) for a small amount of slip (Renard et al, 2012), and at highly stressed frictional asperities during rapid slip (Rice, 2006).…”
Section: Surface Melting and Heating Efficiencymentioning
confidence: 99%